PENERAPAN MANAJEMEN STRATEGI: IMPLEMENTASI, RESISTENSI DAN EVALUASI UNTUK PENINGKATAN MUTU PENDIDIKAN PADA MAN 2 KOTA MALANG - Rina Widjajanti; Mariyo Mariyo (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The research was conducted at MAN 2 Malang City through qualitative descriptive research where the subjects of the research were the head of the madrasa, vice principal of the madrasa, treasurer, administrative staff, madrasa committee and teachers. Data collection techniques through interviews are carried out online and offline, observation and documentation studies. The results showed that the profile of MAN 2 Malang City described 1) the vision, mission, 2) goals, 3) targets and profiles of madrasah resources. Strategy implementation at MAN 2 Malang City is carried out through internal and external school environmental activities which are described through the school's organizational structure, teamwork and division of madrasa tasks, study days and times, financing assets, curriculum, promotion of madrasas, new student admissions, madrasa culture, code of ethics, madrasa policy, geographical, demographic, cultural environment and community appreciation, government policy, development of science and technology, involvement of madrasa committees, supporting or partnering institutions, alumni and strategic implementation in an effort to meet national education standards. Implementation of evaluation at MAN 2 Malang City is carried out continuously involving the highest or top management and madrasah stakeholders both short, medium and long term through madrasah self-evaluation instruments, teachers and benchmarking to improve madrasa performance and education quality.Keywords: Implementation of strategic management, improving the quality of education, madrasasABSTRAK Penelitian dilakukan di MAN 2 Kota Malang melalui penelitian deskriptif kualitatif dimana yang menjadi subyek penelitian adalah kepala madrasah, wakil kepala madrasah, bendahara, tenaga tata usaha, komite madrasah dan guru. Teknik pengumpulan data melalui wawancara dilakukan melalui online dan offline, observasi dan studi dokumentasi. Hasil penelitian menunjukkan bahwa profil MAN 2 Kota Malang mendeskripsikan 1) visi, misi, 2) tujuan, 3) sasaran dan profil sumber daya madrasah. Implementasi strategi pada MAN 2 Kota Malang dilakukan melalui aktivitas lingkungan internal dan eksternal sekolah yang dideskripsikan melalui struktur organisasi sekolah, teamwork dan pembagian tugas madrasah, hari dan waktu belajar, aset pembiayaan, kurikulum, promosi madrasah, penerimaan siswa baru, budaya madrasah, kode etik, kebijakan madrasah, keberadaan lingkungan geografis, demografis, lingkungan budaya dan apresiasi masyarakat, kebijakan pemerintah, perkembangan ilmu pengetahuan dan teknologi, keterlibatan komite madrasah, lembaga pendukung atau yang bermitra, alumni dan implementasi strategik dalam upaya memenuhi standar pendidikan nasional. Pelaksanaan evaluasi pada MAN 2 Kota Malang dilakukan secara terus menerus melibatkan manajemen tertinggi atau puncak dan stakeholder madrasah baik jangka pendek, menengah dan panjang melalui instrumen evaluasi diri madrasah, guru dan benchmarking untuk meningkatkan kinerja madrasah dan mutu pendidikan.Kata kunci: Implementasi manajemen strategi, peningkatan mutu pendidikan, madrasah